ROLE OF AYURVEDIC FORMULATIONS IN AN OVARIAN CYST: A CASE STUDY - Meena, Parmar; Gaurav, Parmar (International Journal of Ayurveda and Pharma Research, 2015)
A female patient of 15 years, came with the complaint of irregular cycle into the OPD which was a diagnosed case of ovarian cyst and took conservative management (Hormonal therapy) for 3 months. After therapy, the Ultrasonography was repeated and the findings were found to be same as before. As the size of cyst was large (60x55x33mm) so, she was advised surgery. But patient was not interested in surgical intervention. Before treatment, the patient was advised of the risks of cyst rupture and instructed to seek care immediately if she becomes symptomatic. Patient was treated with Chanderprabhavati, Kanchnar guggulu, Ashokarishta, Haridrakhand and local sudation for 2 months. It cured the ovarian cyst with symptomatic relief to the patient. But to establish this fact, further study of longer duration and on large sample is required.